Perlindungan Anak Korban Kekerasan Dan Pelecehan Seksual - Zhakila Salsabila Rizky Imani Pulubuhu; Lisnawaty W. Badu; Melisa Towadi (Perkara : Jurnal Ilmu Hukum dan Politik, 2023)
Violence against children in Bonebolango shows a graphic increase which continues to increase every year. As a result, many children who are victims of violence experience deep trauma. Even though the government has revised the Child Protection Act number 23 of 2002 to become the Child Protection Act number 35 of 2014 concerning sanctions for perpetrators of child abuse, in fact it is still not optimal in its implementation against perpetrators of violence. Therefore, this research focuses on efforts to prevent cases of violence against children and the empowerment carried out by the Bonebolago District P2TP2A institution for child victims of violence. This research is categorized as a type of field research using a descriptive qualitative approach. The data sources in this research were counselors at the P2TP2A institution in Malang Regency, which was then carried out using data collection methods in the form of interviews and documentation. Furthermore, data management techniques are carried out by editing, classifying, verifying, analyzing the data. The results of this study indicate, first, the forms of violence that enter the P2TP2A Institute are: a) physical violence; b) psychological violence; c) sexual violence; and d) economic violence. Second, efforts to prevent cases of violence against children carried out by the P2TP2A institution are: a) preventive efforts by conducting counseling outreach; b) educative efforts in the form of scientific activities as well as holding forums on preventing violence and conducting radio broadcasts to provide education about child abuse; c) curative efforts for victims who experience violence by assisting victims in undergoing assistance carried out by counselors; and d) rehabilitative efforts, namely aiming to restore the condition of victims as a result of the violence they experienced, both physically and psychologically and economically. Third, in empowering child victims of violence, the P2TP2A institution prioritizes the psychological condition of the victim first, counselors pay maximum attention to the psychological condition of the victim to be handled and treated as soon as possible to prevent worse psychological symptoms from occurring.